Risk factors for intraventricular hemorrhage in very low birth weight infants in Tehran, Iran - Khodapanahandeh, Fariba; Khosravi, Nastaran; Larijani, Tahereh (The Turkish Journal of Pediatrics, 2008)
Intraventricular hemorrhage (IVH) is an important cause of morbidity and mortality in very low birth weight (VLBW) infants; 80-90% of cases occur between birth and the third day of life. In a retrospective case control clinical study, files of all premature infants with birth weights